No more Sabado nights - Coronel, Shiela (Philippine Center for Investigative Journalism, 1996)
Story of how the women of Tawid Sapa, a slum in the outskirts of Metro Manila, organized themselves against wife-beating, set up a refuge for battered women, and got the government to install electric lines and dig deep wells in their community.